ABR in newborns: Effects of electrode configuration, stimulus rate, and EEG rejection levels on test efficiency. (October 2013) - Stevens, John; Brennan, Siobhan; Gratton, Denise; Campbell, Michael
Abstract: Objective: This study investigated the effect of electrode configuration, stimulus rate, and EEG rejection level on the efficiency of ABR testing in babies. Design: ABR to click stimuli at 40 dB nHL were simultaneously recorded from two electrode configurations, ipsilateral mastoid to high forehead (Mi-Fh) and nape to high forehead (N-Fh), with two EEG rejection levels (± 5 μV and ± 10 μV). Stimulus rates were between 39.1 and 69.1 per second. Efficiency was measured by confidence in the ABR for a given test time. Study sample: Thirty babies who had passed a targeted newborn hearing screen with ABR thresholds ≤ 40 dB nHL. Results: The N-Fh configuration, as expected, gave on average a larger response amplitude compared to the Mi-Fh configuration but was only marginally significantly better in terms of test efficiency. There was no significant effect of stimulus rate on test efficiency between 39.1/s and 59.1/s. The lower ± 5 μV EEG rejection level was more test efficient. Conclusions: This study provides some evidence that, for ABR threshold testing in babies, alternatives of ipsilateral mastoid or nape electrode and a range of stimulus rates have little or no effect on test efficiency. The results support the use of low EEG rejection limits.